Penerapan Algoritma Dijkstra Untuk Menentukan Rute Terbaik Pada Mobile E-Parking Berbasis Sistem Informasi Geografis - Cahyo Prianto; Muh Kusnadi (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Lack of information about the posision of a place and find the best route to get to a destination is complicated, especially looking for a route in finding a parking space. Unavailability of applications that provide information and navigate parking users to find the best route in realtime is a problem that must be answered. Dijkstra's algorithm is one method of solving problems in finding the best route. The Dijkstra algorithm has compared the possible routes to be traversed and calculated every possible distance. The route with the shortest distance would be the best choice This application was built using an Android-based Geographic Information System that utilizes the Google Maps feature as a parking user interface service. This study uses the Java programming language with Android Studio as an IDE (Integrated Development Environment) and the prototyping model is used in developing problem solving and using UML (Unified Modeling Language) as a system design tool. The results that have been achieved from this research is that Dijkstra's algorithm can answer the problem faced by providing the best route navigation from the user's location to the parking lot at the destination